Pensando el “diálogo académico” norte/sur - Chris Krueger (Bolivian Studies Journal, 2012)
This work approaches the complex relation between North American institutions dedicated to the production of knowledge on Bolivia and its homologous Bolivians, emphasizing the fact that nowadays in Bolivia not only an immense intellectual wealth totally established exists, but also a field of emergent knowledge whose reflections and challenges deserve a diffusion in the north. To authorize in the north the theoretical potecial of the debates generated in Bolivia would make the knowledge produced on Bolivia a lot more dynamic and responsible. Inversely, I will also discuss the importance to initiate in Bolivia studies that will lead to understand the complexity of the institutions and societies of the north, that are not neither homogenous nor static, less still automatically reproductive of imperialism.   Este trabajo aborda la compleja relación entre las instituciones norteamericanas dedicadas a la producción de conocimiento sobre Bolivia y sus homólogas bolivianas, destacando el hecho de que hoy día en Bolivia no sólo existe una inmensa riqueza intelectual plenamente establecida, sino también un escenario de conocimientos emergentes cuyas reflexiones y desafíos ameritan una difusión a gran escala en el norte. Autorizar en el norte el potecial teórico de los debates generados en Bolivia haría más dinámico y responsable el conocimiento que el norte produce sobre Bolivia. Inversamente, se discutirá también la importancia de que en Bolivia se inicien estudios conducentes a dimensionar la complejidad de las instituciones y sociedades del norte, que no son ni homogéneas ni estáticas, menos aún automáticamente reproductoras del imperialismo.